Analysis of Product Quality, Price, and Brand Trust on Purchasing Interest of Phonska Plus NPK Fertilizer Retailers in Deli Serdang Regency - Muhamad Ari Wibowo; Erwansyah Erwansyah; Fitra Arlina Nasution (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of product quality, price, and brand trust on purchasing interest of NPK Phonska Plus fertilizer retailers in Deli Serdang Regency. The object of this study was NPK Phonska Plus fertilizer retailers in Deli Serdang Regency. The population and sample of this study amounted to 40 retailers. Data processing used SPSS Version 26. Data testing was carried out using the classical assumption test and multiple linear regression. The calculated t value of product quality was 4.904> t table 1,688 and a significance of 0.000 <0.05, so product quality partially had a positive and significant effect on purchasing interest. The calculated t value of price was 2.708> t table 1.688 and a significance of 0.010 <0.05, so price partially had a positive and significant effect on purchasing interest. The calculated t value of price is 8.643> t table 1.688 and significance 0.000 <0.05, then brand trust has a partial positive and significant effect on purchase interest. The F test results show that the F count is 106.656> F table 2.64 significant value 0.000 <0.005 means that product quality, price and brand trust simultaneously have a significant effect on purchase interest. The R² test result is 0.899 meaning that 89.9% of purchase interest can be obtained and explained by the variables of product quality, price and brand trust.